Aleutian Islands campaign: the strengths and weaknesses of its planning process and execution. - Easley, Jeremy (Fort Leavenworth, KS : US Army Command and General Staff College, 2014)
During the planning and execution of the Aleutian Islands Campaign, what did the commanders and planners do well, and what could they have done differently to reduce the loss of life? An analysis of this campaign reveals the strengths and weaknesses of the planning process, which resulted in a somewhat erratic execution of the plan. Furthermore, this analysis reveals how modern doctrine accounts for the weaknesses exhibited in the planning of this campaign. Examination of this campaign revealed how the "island-hopping" approach enabled the Eleventh Air Force to build combat power during the westward advance, facilitated a strategic turning movement against the Japanese on Kiska, and served as the only viable alternative to assaulting Kiska first. Similarly, the contribution of the Eleventh Air Force provided the only constant and effective pressure on the enemy, expedited the Japanese abandonment of Kiska, and offered crucial reconnaissance and close air support needed during the assault on Attu. On the other hand, the intelligence analysis and estimate did not include accurate maps for use during the Attu assault, resulted in a hasty and drastic change to the assault plan, and ensured the anti-climactic amphibious assault on the abandoned island of Kiska. Finally, by misconstruing Japanese intent and perceiving idleness in the Pacific, political and senior military leaders conducted a flawed strategic assessment, which ended with the expenditure of valuable resources for insignificant gains. Regardless of its strategic insignificance during the war, an analysis of this campaign still proves beneficial for today's operational planners.